2013
DOI: 10.1126/scitranslmed.3006280
|View full text |Cite
|
Sign up to set email alerts
|

A Host-Based RT-PCR Gene Expression Signature to Identify Acute Respiratory Viral Infection

Abstract: Improved ways to diagnose acute respiratory viral infections could decrease inappropriate antibacterial use and serve as a vital triage mechanism in the event of a potential viral pandemic. Measurement of the host response to infection is an alternative to pathogen-based diagnostic testing and may improve diagnostic accuracy. We have developed a host-based assay with a reverse transcription polymerase chain reaction (RT-PCR) TaqMan low-density array (TLDA) platform for classifying respiratory viral infection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 133 publications
(124 citation statements)
references
References 32 publications
3
118
1
1
Order By: Relevance
“…These two genes have been demonstrated to play a critical role in host immune response to viral infection [26]. By profiling gene expression in peripheral blood in response to respiratory viral infection, a recent study showed that these two genes are among a set of host genes differentially expressed upon viral infection [27][28][29]. It is noteworthy that before our work, various SERSbased multiplex DNA detection techniques have been reported [30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 84%
“…These two genes have been demonstrated to play a critical role in host immune response to viral infection [26]. By profiling gene expression in peripheral blood in response to respiratory viral infection, a recent study showed that these two genes are among a set of host genes differentially expressed upon viral infection [27][28][29]. It is noteworthy that before our work, various SERSbased multiplex DNA detection techniques have been reported [30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 84%
“…Instead, a more effective diagnostic would detect early disease, when clinical symptoms might be mild and when treatment would be most effective. Examples include viral respiratory infection (40), VAP (41,42), post-trauma infection (43), and sepsis (44,45). Although none of these particular gene-expression signatures has advanced to clinical use, they exemplify Non-ventilated Ventilated Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…Disease classifiers can be thought of as patterns of biomarker perturbations capable of categorizing individuals into defined clinical groups (10). The process for the development of a gene expression-based disease classifier can be visualized through several broad steps, including a discovery phase to evaluate gene expression changes in the disease state of interest, a classifier generation step, and a platform development step that incorporates the classifier into a clinically usable diagnostic test.…”
Section: Developing Gene Expression-based Classifiers Of Diseasementioning
confidence: 99%
“…This step has historically represented a major barrier, as technologies capable of rapidly and quantitatively measuring large, complex, gene-based biomarker classifiers have not been available. PCR-based platforms are the current gold standard for mRNA analysis of targeted gene expression (10) (Fig. 2).…”
Section: Technology: Moving From the Lab Toward Patient Carementioning
confidence: 99%